Analysis System Design Smoke Monitoring And Temperature Based Arduino Nano - Bestari Putra Lase; Beni Satria; Solly Aryza3 (Sean Institute, 2024)
This research aims to design and analyze a temperature and smoke monitoring system using Arduino Nano as the main microcontroller. This system is equipped with an LM35 temperature sensor and an MQ-2 smoke sensor to detect environmental changes in real-time. Data obtained from the sensor is processed by Arduino Nano and sent via the KYL1020U wireless communication module using radio frequency technology. Information regarding the temperature and smoke concentration is then displayed on the monitor via an application specifically designed for this purpose. System testing was carried out to evaluate sensor accuracy and wireless data transmission reliability. Test results show that the system is able to detect changes in temperature and smoke concentration with high accuracy and send data effectively without any significant delays. In conclusion, the Arduino Nano-based temperature and smoke monitoring system with the LM35, MQ-2 sensor and KYL1020U module is effective and reliable for environmental monitoring applications on various scales. It is hoped that the implementation of this system can increase awareness and response to potential fire hazards and maintain air quality in various environments.